Essays in public food procurement: the case of PNAE in Brazil - Siqueira, Ana Carolina Ferreira de (2023)
In developing countries, smallholders face high transactions costs for accessing food markets. To mitigate this problem, many countries promote the inclusion of on smallholders products in public markets. Since 2009, a federal law requires public schools in Brazil to use at least 30% of their food budgets received from National Education Development Fund (FNDE, acronym in Portuguese) to procure from family farmers. Despite this, many municipalities still buy almost nothing from family farmers, while others are heavily involved in this program. This thesis focuses on understanding the reasons for the differences in compliance with this public policy. It consists of three chapters. In the first one, I perform a bibliometric analysis and review academic articles qualitatively. I identified some positive and negative factors for complying with the 30% rule and divided them into supply features (family farmers production), demand features (governance and education management) and local context (such as GDP per capita). These factors are empirically tested in chapter 2, with secondary population data from FNDE and Brazilian Geography and Statistics Institute (IBGE in Portuguese). I performed ordinary least squares regressions with fixed effects by geographic regions (mesoregions and states). I found that governance characteristics and smallholders products supply are the main drives that can help or hinder this program success. In chapter 3, I investigated whether municipalities that elected mayor from the same party (PT) that created the PNAE are more likely to comply with the 30% rule. I found that mayors may or may not encourage the implementation of the PNAE and this depends on party alignment. This thesis presents a new set of empirical evidence related to the PNAE. First, supply itself may not be an issue for PNAE implementation; however, some details around it, like price and access and smallholders organization may be in the way for municipalities to procure more from family farmers. Second, I provide an alternative explanation for the political incentives of public policy implementation: political alignment.